2018
DOI: 10.1186/s40779-018-0165-6
|View full text |Cite
|
Sign up to set email alerts
|

On-orbit sleep problems of astronauts and countermeasures

Abstract: Sufficient sleep duration and good sleep quality are crucial to ensure normal physical and mental health, cognition and work performance for the common people, as well as astronauts. On-orbit sleep problem is very common among astronauts and has potential detrimental influences on the health of crewmembers and the safety of flight missions. Sleep in space is becoming a new medical research frontier. In this review we summarized on-orbit sleep problems of astronauts and six kinds of causes, and we presented the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…NASA has indicated that mood disorders of astronauts include depression, irritability, anxiety, and frustration. These conditions are regarded as the most severe threats to the space missions, since they compromise the ability of the astronauts to perform tasks under pressure [119], [120]. Several studies have shown that negative as well as extreme positive feelings along with cognitive workload affect behavior, decision-making and performance in extreme environments [121], [122].…”
Section: H) Mood Disorders In Extreme Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…NASA has indicated that mood disorders of astronauts include depression, irritability, anxiety, and frustration. These conditions are regarded as the most severe threats to the space missions, since they compromise the ability of the astronauts to perform tasks under pressure [119], [120]. Several studies have shown that negative as well as extreme positive feelings along with cognitive workload affect behavior, decision-making and performance in extreme environments [121], [122].…”
Section: H) Mood Disorders In Extreme Environmentsmentioning
confidence: 99%
“…Several studies have shown that negative as well as extreme positive feelings along with cognitive workload affect behavior, decision-making and performance in extreme environments [121], [122]. In addition, sleep deprivation and decreased quality of sleep are common in space missions and can result in performance degradation and both cognitive and mental problems [120]. These are reflected in reduced response time and working memory, higher error rates and reduced visual alertness.…”
Section: H) Mood Disorders In Extreme Environmentsmentioning
confidence: 99%
“…It may affect the health of astronauts, so the safety of the mission would be endangered. Six causes for sleep alterations might be (1) factors related to cabin environment, (2) schedule adjustment, (3) impaired sleep discipline, (4) disordered circadian rhythm, (5) unreasonable work arrangement, and (6) mental and/or physical factors [50].…”
Section: Sleepmentioning
confidence: 99%
“…The countermeasures suggested by Wu et al [ 2 ] do not reduce the cosmic ray induced eye interactions. During a deep space mission, astronauts are exposed to galactic cosmic radiation (GCR) as well as solar particle events (SPEs) [ 12 15 ].…”
Section: Light Flashes Circadian Rhythm and Sleep Problemsmentioning
confidence: 99%
“…The findings of a recent National Aeronautics and Space Administration (NASA)-funded study published in the Lancet Neurology journal showed sleep deficiency in astronauts not only during space shuttle and International Space Station (ISS) missions, but also from the start of a three-month preflight training interval [ 1 ]. Wu et al recently published an article entitled “On-orbit sleep problems of astronauts and countermeasures” have addressed the issue of sleep in space as a new medical research frontier [ 2 ]. In their review, the authors discussed the sleep problems of astronauts.…”
Section: Introductionmentioning
confidence: 99%